(untitled) (Agricultural Engineering, 2023)
A developed small scale kenaf spinning and reeling machine was evaluated in this study. The machine uses the principle of the ring spinning technique to produce spun kenaf-yarn (single or double-ply). The machine component includes two 0.5 kW electric motors positioned on a 640×433×10 mm mild steel frame (with speeds of the electric motors controlled by 0.5 kW variable frequency drives), twisting spindle, inlet frustum, feed roller shaft, reeling and spinning shafts, bearings, and a bevel gear. The machine was evaluated using different spinning speeds (90, 100 and 110 rpm), reeling speeds (60, 70 and 80 rpm) and a kenaf sample (Ifeken DI 400). At the spinning and reeling speeds combination of 90 and 80 rev·min−1, the developed machine was able to produce a continuous length of kenaf yarn twisted at 95.5 turns per minute with a production speed of 0.94 m·min−1 at the highest efficiency (88.9%) of the machine. The level of twist of the spun yarn spun provides information on the required twist level for kenaf fibre as deviation from this value was discovered to cause deformation on the spun yarn. This machine was able to reduce the drudgery involved in the production of spun kenaf-yarn and the technology is expected to positively influence kenaf’s growth and utilization in Nigeria.